2015
DOI: 10.1007/s10008-015-3053-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of electrocatalytic characterization of Ti/Sb-SnO2 and Ti/F-PbO2 electrodes

Abstract: Electrocatalytic oxidation is a promising process for degrading toxic and biorefractory organic pollutants in wastewater treatment. Selection of electrode materials is crucial for electrochemical oxidation process. In this study, Ti/F-PbO 2 and Ti/Sb-SnO 2 electrodes were chosen to compare their electrocatalytic characterization, which were prepared by electrodeposition and thermal decomposition method, respectively. The surface morphology and crystal structure of two electrodes were characterized by scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…Although both of them are associated with nonactive anodes, ,, it is not hard to rank two anodes by comparing their capability in removing TOC, COD, and intermediates, which depends on the specific electrode preparation process and the target pollutant. PbO 2 was reported to have a better performance from some studies, , while in the others’ research ,, and our previous work, , Ti/Sb-SnO 2 was found to present a stronger oxidation power, especially in further degrading intermediates. Therefore, combined GC–MS analysis in this study, we deduced that Sb-SnO 2 -based AE coatings offered not only more catalytic sites in increasing the space–time yield but also a stronger oxidation power as the complement of the power of PbO 2 ME in further degrading the intermediates, therefore causing less accumulation of monomers and the diversity of other intermediates.…”
Section: Results and Discussionmentioning
confidence: 56%
“…Although both of them are associated with nonactive anodes, ,, it is not hard to rank two anodes by comparing their capability in removing TOC, COD, and intermediates, which depends on the specific electrode preparation process and the target pollutant. PbO 2 was reported to have a better performance from some studies, , while in the others’ research ,, and our previous work, , Ti/Sb-SnO 2 was found to present a stronger oxidation power, especially in further degrading intermediates. Therefore, combined GC–MS analysis in this study, we deduced that Sb-SnO 2 -based AE coatings offered not only more catalytic sites in increasing the space–time yield but also a stronger oxidation power as the complement of the power of PbO 2 ME in further degrading the intermediates, therefore causing less accumulation of monomers and the diversity of other intermediates.…”
Section: Results and Discussionmentioning
confidence: 56%
“…This negative impedance behavior is due to the oxidation removal of CO from the catalyst surface and the recovery of the catalytic active sites. [33,36,37] In the potential range of À0.10-0 V ( Figure 9C,F www.advancedsciencenews.com www.entechnol.de transfer on the Pt-CdS QDs/LTO electrode in the methanol oxidation process under the photo-assistance.…”
Section: Resultsmentioning
confidence: 99%
“…The electron transfer kinetics of methanol oxidation on the Pt-CdS QDs/LTO electrode with and without visible light irradiation were studied using EIS at various potentials in the range of 0-0.4 V. As shown in Figure 9A, from À0.4 to À0.25 V, the diameters of the impedance arcs (DIAs) decrease rapidly with an increase in potential under light irradiation, suggesting that more and more active sites are available for methanol oxidation due to the oxidation removal of CO intermediate species, which are generated from methanol dehydrogenation at lower potentials. [33,36,37] When the potential continues to increase ( Figure 9B), the DIA begins to increase due to the poisoning and oxidation of catalyst at higher potentials. However, the arc suddenly reversed to the second quadrant at À0.15 V of the Pt-CdS QDs/LTO electrode under light irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…The distance between the two electrodes was 3 cm. Effects of coating times (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), current density (10-25 mA cm À2 ), electrolyte concentration (10-40 g L À1 ), initial concentration (10-80 mg L À1 ), and pH value (3-9) on degradation were investigated. During experiments, samples were taken every 15 min, and UV-vis Spectrophotometer (TU-1901, Beijing, China) was mainly used to monitor the removal rate of CIP in terms of variances in the absorbance, and the main absorption peak (l max ) located at 275 nm.…”
Section: Electrochemical Degradation Experimentsmentioning
confidence: 99%
“…17 The anode materials are vital for electrochemical oxidation because they determine the formation of hydroxyl radicals. 18 The electrode materials, including SnO 2 , 19 PbO 2 , 20 and boron doped diamond, 21 had been widely used in wastewater treatment. Among them, the Sb-doped SnO 2 electrode has a wonderful application prospect due to its excellent electrochemical activity, chemical stability, and electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%